2018
DOI: 10.1177/0892705718759390
|View full text |Cite
|
Sign up to set email alerts
|

Development of multifunctional nanocomposites with 3-D printing additive manufacturing and low graphene loading

Abstract: Fused filament fabrication (FFF) or fused deposition modeling is an additive manufacturing (AM) process commonly used for geometric modeling and rapid prototyping of parts called three-dimensional (3-D) printing. Commonly used thermoplastic materials in FFF 3-D printing AM are acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and polybutylene terephthalate (PBT). However, these materials exhibit relatively low strength and toughness. Therefore, it is desirable to improve various properties of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…The other key factors that need to be considered to avoid agglomeration and uneven dispersion are surface homogenization and the concentration of the incorporated NDs. The properties of PMMA [ 9 , 10 ], epoxy [ 14 , 31 ], and poly (vinyl alcohol) [ 32 ] were reportedly improved with less than 0.2 wt% ND incorporation. Therefore, in the present study, both the ND- and A-ND-incorporated nanocomposites were fabricated with a 0.1 wt% ND concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The other key factors that need to be considered to avoid agglomeration and uneven dispersion are surface homogenization and the concentration of the incorporated NDs. The properties of PMMA [ 9 , 10 ], epoxy [ 14 , 31 ], and poly (vinyl alcohol) [ 32 ] were reportedly improved with less than 0.2 wt% ND incorporation. Therefore, in the present study, both the ND- and A-ND-incorporated nanocomposites were fabricated with a 0.1 wt% ND concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Although biocompatibility of graphene-reinforced PLA has been proven in previous studies, its potential application in load-bearing structures and the resultant performance under different loading conditions need to be evaluated [18,42]. Recently, a few studies have reported the successful development of graphene-based reinforced polymer composites for 3D printing [43,44,45]. However, in composites, the main challenge is to understand how to transfer the properties of graphene from the nanoscale to the macroscale.…”
Section: Introductionmentioning
confidence: 99%
“…High strength and thermal resistant materials such as polyetherimide (PEI/ULTEM) [3] and polyether ether ketone (PEEK) find printability with high-temperature printers expand the applicability of FDM [3]. The properties of FDM print components can improve by composite filaments [4][5][6] in the form of polymer blends [7], polymer matrix composites, fibre reinforced composites and polymer-ceramic composites [8][9][10][11]. The introduction of more printable filaments has elaborated the application of FDM components in the field of automotive [12,13], aerospace [14,15], medical [16] and manufacturing [17][18][19].…”
Section: Introductionmentioning
confidence: 99%